MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI PENGGUNAAN STRATEGI PEMBELAJARAN JIGSAW PADA MATERI SEGIEMPAT DAN SEGITIGA - Maryati Maryati (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
This research was conducted at MTsN 2 Bireuen, Central Aceh Regency, Aceh Province. In this study, the research subjects were selected by conducting random sampling by means of a lottery (Syahrum, 2009), first preparing as many pieces of paper as there were, then the pieces of paper were put into a box and taken at random, one of the papers was taken as the research sample. The paper taken is for Class VII-2 Semester 2 which contains 22 people. The object of this research is the application of jigsaw learning strategies to improve students' mathematics learning outcomes on the subject of quadrilaterals and triangles. The model in this research is Classroom Action Research (CAR), which uses Kemmis and Mc's CAR model. Taggart. This research has stages in the form of a cycle. The results of the study of the jigsaw learning strategy in mathematics subjects Class VII-2 MTsN 2 Bireuen can be said that the increase in student learning outcomes. This increase can be seen from the average value of the class has increased. This can be shown from the results of the evaluation that has been carried out to increase student learning outcomes which were originally the average value of 57.73 before the action and the first cycle increased to 69.09. While in the second cycle the increase in learning outcomes to 79.77. This shows that 86.36% of students are successful in learning mathematics by using jigsaw learning strategies.